2018
DOI: 10.1177/2053434518800884
|View full text |Cite
|
Sign up to set email alerts
|

A system-wide transformation towards integrated care in the Basque Country: A realist evaluation

Abstract: Introduction: In 2010, in a context of severe economic recession, the Basque Government launched the Strategy to tackle the challenge of chronicity in the Basque Country to transform the Basque health system to cope with the challenges of chronicity, ageing, health system fragmentation and sustainability in the long run. Methods: A realist evaluation has been conducted, and through a combination of research methods, information has been analysed to identify context, mechanisms and outcomes. The research provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…However, expanding in the direction of social care and upscaling local initiatives is still unusual as many challenges exist due to misalignment in culture, governance, and information infrastructure [29,30]. International evidence shows that the use of feedback information and a shared savings model like in the Healthy Kinzigtal region in Germany [31], cultural integration in local initiatives in Finland [32] and New Zealand [33] and multi-level policy interventions in the Basque region [34,35] are longterm investments that can boost performance of integrated care networks. The strengths of a network like the Krijtmolen Alliantie is their 10 year investment in mutual trust and vision between health and social care providers to build the foundation of its integrating care network.…”
Section: Discussionmentioning
confidence: 99%
“…However, expanding in the direction of social care and upscaling local initiatives is still unusual as many challenges exist due to misalignment in culture, governance, and information infrastructure [29,30]. International evidence shows that the use of feedback information and a shared savings model like in the Healthy Kinzigtal region in Germany [31], cultural integration in local initiatives in Finland [32] and New Zealand [33] and multi-level policy interventions in the Basque region [34,35] are longterm investments that can boost performance of integrated care networks. The strengths of a network like the Krijtmolen Alliantie is their 10 year investment in mutual trust and vision between health and social care providers to build the foundation of its integrating care network.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the health system should promote the right continuity and coordination of care for individuals suffering from mental health conditions and other chronic conditions [ 10 , 72 ]. Additionally, inequalities are being alleviated through the co-creation of value in the design of public provision of both health and social services addressed to those in need, as it has been shown that social disconnectedness could affect perceived isolation and symptoms of depression and anxiety among the elderly [ 73 , 74 ]. In the absence of well-designed access to social services and social care, an increase in socioeconomic inequalities can be expected, especially for the elderly, as a more vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…Managers and decision-makers should not take them as ‘given’ but as something that can be tackled with policies and well-targeted interventions, resulting in a pro-poor orientation like the case of the Basque Country has shown. This Region has adopted a system-wide transformation towards integrated care [ 74 ], oriented to be based on primary care in the community; good integration of primary care and mental health; and successful implementation of a model of comprehensive care for chronic conditions, promoting the right continuity and coordination of care for individuals suffering mental health conditions and other chronic conditions. The emerging mental health delivery model offers excellent potential for international comparisons and benchlearning.…”
Section: Discussionmentioning
confidence: 99%
“…Over recent decades, there have been numerous examples of international integrated care models focusing on the needs of community-dwelling older people that have sought to embed these factors and tackle the implementation challenges they bring with varying degrees of success (WHO, 2016). Examples of the most cited include the Canadian PRISMA model (Program of Research to Integrate the Services for the Maintenance of Autonomy) (MacAdam, 2015), the Basque Country integrated care model (Urtaran-Laresgoiti et al , 2018), the Buurtzorg model originating in the Netherlands (Monsen and Deblok, 2013) and the population-based Kaiser Permanente in the USA (Pines et al , 2015). Looking across the models, it would appear that there are a set of components and delivery strategies that are associated with successful integrated care models (WHO, 2016) including the characteristics highlighted by our research.…”
Section: Discussionmentioning
confidence: 99%